Segetal Vegetation of Soybean Crops Underthe Influence of Biological and Chemical Preparations - Карпенко, В. П.; Івасюк, Ю. І.; Притуляк, Р. М. (Podilian Bulletin: Agriculture, Engineering, Economics, 2017)
The results of observations concerning the impact of different rates of herbicide Fabian (90;100 and 110 g/ha); plant growth regulator Rehoplant (250 ml/t preplanting seed cultivation; 50 ml/ha – postgermination application) and microbiological preparation Ryzobofit (100 ml/t seeds) on segetal vegetation of soybeans were established. The optimal rates and ways of application of preparations promoting the most effective quantity and weight reduction of segetal vegetation in soybean crops were determined. This arrangement provides effective control of segetal vegetation in crops of soybeans resulting increase competitiveness. 30 days after the introduction of preparetion were recorded the highest percentage of destroyed weeds was observed for use in crops of soybeans herbicide Fabian in rates 90; 100 and 110 g/ha together with plant growth regulators Rehoplant normal 50 ml/ha; made against the backdrop of pre seed treatment mixture Ryzobofit with Rehoplant and where the number of weeds was destroyed by the number 91; 92 and 92% by weight – 90; 90 and 91% respectively. Accounting segetal vegetation soybean crops before harvest showed that the highest percentage of weeding provide options experiment combined use of herbicide Fabian 90–110 g/ha of plant growth regulators Rehoplant against the background pre-treatment of seeds Ryzobofit microbiological agents in combination with plant growth regulators Rehoplant where it was noted fewest weeds 12-10 pcs./m2 with weight 100;6–95;3 g/m2; corresponding to the number destroyed them up to 90–92%; and weight – 89–90%.